Phenotypic and Genotypic Characterization of Extended Spectrum Beta-Lactamase-Producing Clinical Isolates of Escherichia coli and Klebsiella pneumoniae in Two Kenyan Facilities: A National Referral and a Level Five Hospital - Sylvia M. Maveke; Gabriel O. Aboge; Laetitia W. Kanja; Alfred O. Mainga; Naftaly Gachau; Beatrice W. Muchira; Gervason A. Moriasi (International Journal of Microbiology)
Background. The emergence of antimicrobial resistance (AMR) and multidrug resistance (MDR) among Escherichia coli and Klebsiella pneumoniae, especially through the production of extended spectrum β-lactamases (ESBLs), limits therapeutic options and poses a significant public health threat. Objective. The aim of this study was to assess the phenotypic and genetic determinants of antimicrobial resistance of ESBL-producing Escherichia coli and Klebsiella pneumoniae isolates from patient samples in two Kenyan Hospitals. Methods. We collected 138 E. coli and 127 K. pneumoniae isolates from various clinical specimens at the two health facilities from January 2020 to February 2021. The isolates’ ESBL production and antibiotic susceptibility were phenotypically confirmed using a standard procedure. Molecular analysis was done through conventional polymerase chain reaction (PCR) with appropriate primers for gadA, rpoB, blaTEM, blaSHV, blaOXA, blaCTX-M-group-1, blaCTX-M-group-2, blaCTX-M-group-9, and blaCTX-M-group-8/25 genes, sequencing and BLASTn analysis. Results. Most E. coli (82.6%) and K. pneumoniae (92.9%) isolates were ESBL producers, with the highest resistance was against ceftriaxone (69.6% among E. coli and 91.3% among K. pneumoniae) and amoxicillin/clavulanic acid (70.9% among K. pneumoniae). The frequency of MDR was 39.9% among E. coli and 13.4% among K. pneumoniae isolates. The commonest MDR phenotypes among the E. coli isolates were CRO-FEP-AZM-LVX and CRO-AZM-LVX, while the FOX-CRO-AMC-MI-TGC-FM, FOX-CRO-FEP-AMC-TZP-AZM-LVX-MI and CRO-AMC-TZP-AZM-MI were the most frequent among K. pneumoniae isolates. Notably, the FOX-CRO-FEP-AMC-TZP-AZM-LVX-MI phenotype was observed in ESBL-positive and ESBL-negative K. pneumoniae isolates. The most frequent ESBL genes were blaTEM (42%), blaSHV (40.6%), and blaOXA (36.2%) among E. coli, and blaTEM (89%), blaSHV (82.7%), blaOXA (76.4%), and blaCTX-M-group-1 (72.5%) were most frequent ESBL genes among K. pneumoniae isolates. The blaSHV and blaOXA and blaTEM genotypes were predominantly associated with FOX-CRO-FEP-MEM and CRO-FEP multidrug resistance (MDR) and CRO antimicrobial resistance (AMR) phenotypes, among E. coli isolates from Embu Level V (16.7%) and Kenyatta National Hospital (7.0%), respectively. Conclusions. The high proportion of ESBL-producing E. coli and K. pneumoniae isolates increases the utilization of last-resort antibiotics, jeopardizing antimicrobial chemotherapy. Furthermore, the antimicrobial resistance patterns exhibited towards extended-spectrum cephalosporins, beta-lactam/beta-lactamase inhibitor combinations, fluoroquinolones, and macrolides show the risk of co-resistance associated with ESBL-producing isolates responsible for MDR. Hence, there is a need for regular surveillance and implementation of infection prevention and control strategies and antimicrobial stewardship programs.